1988
DOI: 10.1021/bi00424a003
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage oxidation of L-arginine to nitrite and nitrate: nitric oxide is an intermediate

Abstract: Previous studies have shown that murine macrophages immunostimulated with interferon gamma and Escherichia coli lipopolysaccharide synthesize NO2-, NO3-, and citrulline from L-arginine by oxidation of one of the two chemically equivalent guanido nitrogens. The enzymatic activity for this very unusual reaction was found in the 100,000g supernatant isolated from activated RAW 264.7 cells and was totally absent in unstimulated cells. This activity requires NADPH and L-arginine and is enhanced by Mg2+. When the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
640
2
21

Year Published

1989
1989
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,533 publications
(689 citation statements)
references
References 20 publications
17
640
2
21
Order By: Relevance
“…Hydrogen peroxide was purchased from J.T. Baker (Deventer, Holland); [2,3,4,5] The macrophage cell line, NR8383 was kindly provided by R.J. Helmke, (Dept of Pediatrics, University of Texas Health Science Center, San Antonio, Texas, USA). Klebsiella Pneumoniae were a kind gift from J. van Amsterdam (Rijksinstituut voor Volksgezondheid en Milieu, Bilthoven, the Netherlands).…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen peroxide was purchased from J.T. Baker (Deventer, Holland); [2,3,4,5] The macrophage cell line, NR8383 was kindly provided by R.J. Helmke, (Dept of Pediatrics, University of Texas Health Science Center, San Antonio, Texas, USA). Klebsiella Pneumoniae were a kind gift from J. van Amsterdam (Rijksinstituut voor Volksgezondheid en Milieu, Bilthoven, the Netherlands).…”
Section: Chemicalsmentioning
confidence: 99%
“…Nitric oxide (NO) is a free radical that is known to have an important function as mediator in several biological processes amongst which, vasorelaxation [1,2], cellmediated immune responses [3,4], inhibition of platelet aggregation [5] and neurotransmission [6] are extensively investigated. The formation of NO has been described in many mammalian cell types and can be ascribed to three isoforms of nitric oxide synthase (NOS), all of which oxidize L-arginine to L-citrulline.…”
mentioning
confidence: 99%
“…In activated macrophages generation of NO by inducible NO synthase (iNOS) is critically dependent on extracellular arginine (2,4,5), despite reports that activated cells contain high intracellular arginine levels (1,6). N G -derivatized analogues of L-arginine are potent inhibitors of iNOS, and their rank order of potency has been attributed to different NOS isoforms and/or their differential rates of cellular uptake (7,8).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Inducible NOS (iNOS) is calcium-independent and produces large amounts of NO which may mediate cGMP-independent cytotoxicity against microorganisms and tumor cells (Stuehr and Nathan, 1989). iNOS is found in a variety of cells such as macrophages (Marletta et al, 1988), endothelial cells (Kilbourn and Belloni, 1990) and glial cells . While all three types of NOS may be expressed in astrocytomas (Cobbs et al, 1995), expression of iNOS was only observed in high-grade tumors and mainly restricted to endothelial cells within the tumor.…”
Section: Introductionmentioning
confidence: 99%